2006
DOI: 10.1103/physreve.73.016301
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of instability in liquid flow down an inclined plane by a deformable solid layer

Abstract: The linear stability of a liquid layer flowing down an inclined plane lined with a deformable, viscoelastic solid layer is analyzed in order to determine the effect of the elastohydrodynamic coupling between the liquid flow and solid deformation on the free-surface instability in the liquid layer. The stability of this two-layer system is characterized by two qualitatively different interfacial instability modes: In the absence of the deformable solid layer, the free surface of the liquid film undergoes a long… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
22
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 15 publications
2
22
0
Order By: Relevance
“…These studies, however, employed the linear elastic model 15 to describe the deformation in the solid, which is valid only when the deformation gradients in the solid are small. In a recent paper, Gkanis and Kumar 16 used the more rigorous neo-Hookean model 17,18 and demonstrated in the creeping-flow limit that the predictions from the two solid models could be significantly different for the stability of flow down an inclined plane covered with a deformable solid, and noted that the earlier predictions of instability suppression 11,12 must be reexamined using the neo-Hookean solid model. The freesurface instability is absent in the creeping-flow limit, so it is necessary to consider nonzero Reynolds number in order to analyze the suppression of free-surface instability by the deformable solid.…”
Section: Introductionmentioning
confidence: 96%
See 4 more Smart Citations
“…These studies, however, employed the linear elastic model 15 to describe the deformation in the solid, which is valid only when the deformation gradients in the solid are small. In a recent paper, Gkanis and Kumar 16 used the more rigorous neo-Hookean model 17,18 and demonstrated in the creeping-flow limit that the predictions from the two solid models could be significantly different for the stability of flow down an inclined plane covered with a deformable solid, and noted that the earlier predictions of instability suppression 11,12 must be reexamined using the neo-Hookean solid model. The freesurface instability is absent in the creeping-flow limit, so it is necessary to consider nonzero Reynolds number in order to analyze the suppression of free-surface instability by the deformable solid.…”
Section: Introductionmentioning
confidence: 96%
“…More recently, Gkanis and Kumar 16 studied the same configuration as in Ref. 12, but used the neo-Hookean model to describe the solid deformation, and considered the creeping-flow limit where the GL mode instability is absent in rigid surfaces. Their results showed that the solid deformability destabilizes only one of the two interfacial modes, which they identified as the LS mode ͑in the present nomenclature͒.…”
Section: Introductionmentioning
confidence: 97%
See 3 more Smart Citations